2018
DOI: 10.1590/0103-8478cr20180123
|View full text |Cite
|
Sign up to set email alerts
|

Milk composition of Holstein cows: a retrospective study

Abstract: Worldwide, milk analysis is an satisfactory measurement of milk quality on dairy farms. Milk composition is the base for payment systems, so knowledge of its characteristics at different periods is essential for modern dairy producer. The aim of the study was to evaluate the effects of year, season, stage of lactation, and lactation number on variations in milk yield and composition of Holstein cows (n=148,604). Milk yield estimated by multiple regression was 25,50L/cow/day. Winter was the season with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
4
16
0
4
Order By: Relevance
“…The synthetic capacity of milk components was evaluated on yearly average by analysing the content and daily yield of milk protein and fat in relation to the nutrient intake according to the stage of lactation in dairy cows. The confirmed increase in the milk protein content during lactation is consistent with a previous study by Bondan et al (2018). The decrease in the milk yield in continuous lactation causes the protein content to remain more concentrated (Idamokoro et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The synthetic capacity of milk components was evaluated on yearly average by analysing the content and daily yield of milk protein and fat in relation to the nutrient intake according to the stage of lactation in dairy cows. The confirmed increase in the milk protein content during lactation is consistent with a previous study by Bondan et al (2018). The decrease in the milk yield in continuous lactation causes the protein content to remain more concentrated (Idamokoro et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the SCC of rabbit milk was slightly correlated with casein but not with any of the other analyzed chemical compounds. The researchers Bondan et al [60] analyzed the relationship between the milk yield of Holstein cows and the chemical composition of their milk. The values of correlation coefficients were low to medium degree.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of production were found for Holstein cows raised in other Brazilian regions. In the southern region, for instance, Silva et al (2011), Ludovico et al (2015) and Bondan et al (2018) found an average production of 28.62, 31.78 and 25.50 kg/cow/day, respectively. In the southeast region, Bignardi et al (2015) and Villadiego et al (2016) recorded an average value of 24.25 and 22.9 kg/cow/day, respectively.…”
Section: Resultsmentioning
confidence: 97%